2019
DOI: 10.1002/smj.3098
|View full text |Cite
|
Sign up to set email alerts
|

Navigating geographic and cultural distances in international expansion: The paradoxical roles of firm size, age, and ownership

Abstract: Research Summary While geographic and cultural distances deter firms' international expansion, they do so via different mechanisms, such that firms with advantages in overcoming one‐dimension may face disadvantages in overcoming the other. Larger, older, and state‐owned firms have better access to resources in their home countries than smaller, younger, and non‐state‐owned firms, and thus are less concerned about the high operating costs associated with larger geographic distances. However, they are less adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 129 publications
0
68
2
Order By: Relevance
“…In contrast, larger cultural distance indicates more barriers rooted in informal rules which may be overcome with substantive government support from agencies located in the host countries. It should be pointed out that extant literature shows negative direct effects of cultural distance on FDI location choice of Chinese firms (e.g., Kang & Jiang, 2012;Li, Zhang, & Shi, 2019). This study suggests that culturally distant locations are likely the right circumstances for Chinese firms to leverage the government support despite the expected challenges arising from unfamiliarity with informal rules.…”
Section: Discussionmentioning
confidence: 66%
“…In contrast, larger cultural distance indicates more barriers rooted in informal rules which may be overcome with substantive government support from agencies located in the host countries. It should be pointed out that extant literature shows negative direct effects of cultural distance on FDI location choice of Chinese firms (e.g., Kang & Jiang, 2012;Li, Zhang, & Shi, 2019). This study suggests that culturally distant locations are likely the right circumstances for Chinese firms to leverage the government support despite the expected challenges arising from unfamiliarity with informal rules.…”
Section: Discussionmentioning
confidence: 66%
“…Second, based on the same reasoning, we controlled for firms' age and firms' size, which are closely related to the internationalization growth (Prashantham et al ., 2020). Third, we controlled for firms' overseas annual sales in the previous three years and internationalization experience, both of which reflect enterprises' international development status (Li et al ., 2020). Finally, the industry, as well as the type of international business, can be expected to affect firms' global expansion process (Sharma and Kesner, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…The Uppsala model advocates that the impact of cultural differences will gradually decrease as organisations acquire professional knowledge on the international stage (Hakanson and Ambos, 2010). So, we can see that cultural distance hinders international expansion, enterprises are unlikely to expand to countries with a higher level of cultural distance since they need to change their organisational practices to adapt to the culture of host country (Li et al, 2020). On the contrary, many studies have found that there is a positive correlation between cultural distance and performance.…”
Section: Ccsm 283mentioning
confidence: 99%